The Glass palace chronicle of the kings of Burma - Phe Moṅʻ Taṅʻ, Ūʺ, 1888-1973; Luce, G. H. (Gordon Hannington), 1889-1979 (Rangoon University Press, 1960)
History of Burma, from early till the end of 13th century.